Méthode pour un plan à moyen terme - Falkowski, M. (Canadian Journal of Higher Education, 1978)
The University of Geneva has at its disposal an innovative system of medium range planning in the form of 4-year development plans. These plans, written into the "Loi sur l'Université" (the University Act) and dated May 26, 1973, are administered by the Commission de développement (C.D.) (Development Commission), a standing advisory body to the vice-chancellor's office. The C.D. is made up of representatives of faculties and schools and is chaired by a vice-chancellor who also heads the Service de développement (S.D.) (Development Service) - a team of three researchers and their secretarial office. The S.D. is under the central administration and is responsible for studies, development of the plan and institutional research. The role of the C.D. is specific and is not limited only to planning. The C.D. lends itself well to university forecasting and, because of this, the qualitative and quantitative aspects of development are constantly compared. Thus, the term "development" covers a wide field of investigation and is not identified with a mere planning technique. Through this approach, two other ends are also sought: on the one hand, bringing academic structures into line with administrative ones, fan extremely important aspect in a typical European university) and. on the other hand, coordinating medium and long range planning (forecasting the number of students, space etc. J The article refers to the planning experience of the University of Geneva and is based, in the main, on the chapter entitled "Méthode " of the second development plan for the years 1977-1980.